Розробка компонентів інформаційної системи «магазин велотоварів» - Репринцев, М. В. (ХНУРЕ, 2024)
The application of advanced technologies plays an important role in the modernization of trade, in particular in the field of bicycle business. Bicycle shops can significantly improve their productivity and optimize customer interactions by using digital tools to automate inventory, order management and financial accounting. The use of e-commerce in the bicycle industry opens up new opportunities for retailers to optimize internal processes and expand the range of bicycle products offered to potential customers.
Keywords: інтерфейс користувача; база даних товарів; управління замовленнями; система оплати; адміністрування користувачів